Relation of postmortem protease activity to tenderness in buffalo meat and Brahman beef - M. Hirabayashi; K. Chikuni; S. Muroya; T. Fujihara; L. C. Cruz; J.R. V. Herrera; R.M. Lapitan; A.N. Del Barrio; K.E. Neath; Y. Kanai (Italian Journal of Animal Science, 2010)
We previously showed that meat from crossbred water buffalo had significantly higher tenderness than beef from crossbred Brahman cattle of the same age, gender, and diet. Extensive studies on meat tenderness have indicated that proteases degrade muscle fibre proteins during postmortem storage, leading to weakening of the myofibrillar structure and an increase in tenderness. Thus, we investigated the difference in protease activity immediately postmortem, in order to explain the difference in tenderness between buffalo meat and beef. Five female crossbred water-buffalo (Philippine Carabao x Bulgarian Murrah) and five female crossbred cattle (Brahman x Philippine Native) were slaughtered at 30 months of age, and Longissimus thoracis muscle was sampled immediately post-slaughter. Protease activity at different pH levels and the effect of various inhibitors on protease activity were examined. Results showed that buffalo meat had significantly higher protease activity compared to beef, and calpain inhibitor 1 was the most effective inhibitor. As calpain inhibitor 1 is a specific inhibitor of calpain 1 and 2, the results suggest that higher calpain activity in buffalo meat was responsible for the higher tenderness of buffalo meat compared to Brahman beef.